Michelson interferometer system with acoustic optic filter and fiber Bragg grating for reduction of four-wave mixing - de Sousa, Fabio Barros; de Oliveira, Jorge Everaldo; de Sousa, Fiterlinge Martins; Costa, Marcio Benedito Caldas; de Oliveira, Osmar Tharlles Borges; Oliveira, Jackson Moreira; Martins, Elizete Sabino; Costa, Marcos Benedito Caldas (Scientia Plena, 2019)
In this paper a simplified design and efficient of a Michelson Interferometer (MI) system is presented, capable of reducing the Four-Wave Mixing (FWM) effects, using fiber Bragg grating and acoustic optic filter (FBG and AOF) with the aid of a highly non-linear photonic crystal fiber (HNL-PCF). The analysis of the MI system based in FBG and AOF was performed according to the effect of fiber length and input power by performance metrics: Optical Spectrum, maximum Quality factor (max. Q-factor), minimum bit error rate (min. BER), eye height, optical signal-to-noise ratio (OSNR) and timing jitter. The numerical simulation results showed that the MI system with FBG and AOF maintained a good signal performance, with Q-factor equal to 33.3 even after 100 km of single mode fiber (SMF) and with downstream signal power by up to 10 dBm.